Dentinal Tubule Penetrability and Bond Strength of Two Novel Calcium Silicate-Based Root Canal Sealers - Shieh, Karissa; Yang, Jack; Zhu, Elsa Heng; Peters, Ove Andreas; Hosseinpour, Sepanta (Materials, 2023)
Background: Once the chemo-mechanical preparation of root canals is finished, achieving a complete seal of the root canal system becomes crucial in determining the long-term success of endodontic treatment. The important goals of root canal obturation are to minimize leakage and achieve an adequate seal. Thus, a material that possesses satisfactory mechanical characteristics, is biocompatible, and has the ability to penetrate the dentine tubules adequately is needed. Aim: This study aimed to compare the penetrability and bond strength between two calcium silicate-based sealers and an epoxy resin-based sealer, as well as examine the relationship between penetrability and bond strength for the different sealers. Method and materials: Thirty-nine recently extracted single-rooted human premolar teeth were instrumented and divided evenly into three groups (n = 13), according to the sealer used for obturation: AH Plus Jet, EndoSequence, and AH Plus Bioceramic Sealer. Three teeth (30 slices) were randomly selected out of each for analysis using confocal laser scanning microscopy to assess penetrability. The remaining ten teeth (90 slices) in each group were subject to push-out tests using a universal testing machine. All teeth were sectioned into nine transverse slices of 0.9 mm thickness for their respective tests (apical, middle, coronal). Results: AH Plus Jet exhibited significantly lower penetrability and significantly higher bond strength compared to EndoSequence BC sealer (p = 0.002) and AH Plus Bioceramic Sealer (p = 0.006). There was no significant difference between EndoSequence BC sealer and AH Plus Bioceramic Sealer in terms of either penetrability or bond strength. No correlation was found between penetrability and bond strength. Conclusions: Within the limitation of this study and regardless of the location in the canal, the bioceramic based root canal sealers appeared to perform better than the epoxy resin-based sealer in terms of dentinal penetration rate. Further studies are required to compare other biomechanical properties of bioceramic sealers including setting characteristics and bacterial leakage.